2009
DOI: 10.1021/om900763y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Wiberg’s Tetrasilatetrahedrane (tBu3Si)4Si4 by a One-Pot Procedure

Abstract: A one-pot synthesis of the tetrasilatetrahedrane (tBu 3 Si) 4 Si 4 was achieved by the reaction of HSiCl 3 and Na[SitBu 3 ]. In this reaction the silane tBu 3 SiH was obtained along with (tBu 3 Si) 4 Si 4 and tBu 3 SiSitBu 3 . The tetrasilatetrahedrane (tBu 3 Si) 4 Si 4 was also obtained via a one-pot approach by treatment of Cl 3 SiSiCl 3 or Cl 3 SiSiCl 2 SiCl 3 with Na-[SitBu 3 ]. In the reaction of HSiCl 3 with Na[SitBu 3 ], two molecules of the tetrasilatetrahedrane (tBu 3 Si) 4 Si 4 crystallize together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…The formation of isolable amounts of 5 starting from SiCl 4 is remarkable, since the state‐of‐the art educts for the synthesis of neo ‐Si 5 Cl 12 are Si 2 Cl 6 or Si 3 Cl 8 ,. Previously reported related reactions strongly suggest that dichlorosilylene is a likely intermediate in the course of the formation of 5 in the present case. A plausible mechanism responsible for the unexpected formation of 5 is given in Scheme .…”
Section: Methodssupporting
confidence: 79%
“…The formation of isolable amounts of 5 starting from SiCl 4 is remarkable, since the state‐of‐the art educts for the synthesis of neo ‐Si 5 Cl 12 are Si 2 Cl 6 or Si 3 Cl 8 ,. Previously reported related reactions strongly suggest that dichlorosilylene is a likely intermediate in the course of the formation of 5 in the present case. A plausible mechanism responsible for the unexpected formation of 5 is given in Scheme .…”
Section: Methodssupporting
confidence: 79%
“…[6] However, our research group has recently found out that the reaction of 1 with two equivalents of NaA C H T U N G T R E N N U N G [SitBu 3 ] leads to different products. [7,8] Instead of displaying signals for the substitution product (tBu 3 Si)SiCl 2 SiCl 2 A C H T U N G T R E N N U N G (SitBu 3 ), the 29 Si NMR spectrum of the reaction mixture showed resonances resulting from tetrasilatetrahedrane Si 4 A C H T U N G T R E N N U N G (SitBu 3 ) 4 , disilane tBu 3 SiSitBu 3 , chlorosilane tBu 3 SiCl, as well as polychlorosilanes such as neopentasilane 3. [8] Obviously, this implies that a degradation reaction of 1 has taken place, which involves the liberation of SiCl 2 .…”
mentioning
confidence: 99%
“…[7,8] Instead of displaying signals for the substitution product (tBu 3 Si)SiCl 2 SiCl 2 A C H T U N G T R E N N U N G (SitBu 3 ), the 29 Si NMR spectrum of the reaction mixture showed resonances resulting from tetrasilatetrahedrane Si 4 A C H T U N G T R E N N U N G (SitBu 3 ) 4 , disilane tBu 3 SiSitBu 3 , chlorosilane tBu 3 SiCl, as well as polychlorosilanes such as neopentasilane 3. [8] Obviously, this implies that a degradation reaction of 1 has taken place, which involves the liberation of SiCl 2 . In this context, we note that 2 reacts with NaA C H T U N G T R E N N U N G [SitBu 3 ] in an analogous manner, yielding the same products as the reaction of 1 with NaA C H T U N G T R E N N U N G [SitBu 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, the reaction of Si 2 Cl 6 with amines such as NMe 3 leading to Si(SiCl 3 ) 4 and SiCl 4 has been the subject of numerous studies . Recently, we have repeated the reaction of Si 2 Cl 6 with catalytic amounts of NMe 3 , NMe 2 Et or NEt 3 and found it fully reproducible .…”
Section: Introductionmentioning
confidence: 97%